Supercritical CO2 extraction of Aurantiochytrium sp. biomass for the enhanced recovery of omega-3 fatty acids and phenolic compounds - Melo, M.M.R. de (2020)
The microalgae Aurantiochytrium sp. is a strong alternative source of ω-3 fatty acids, including ocosahexaenoic acid (DHA). This work encompasses the optimization of SFE conditions to maximize the total extraction yield (ηTotal), DHA content (CDHA), total phenolics content (TPC), and antioxidant capacity (AOC) of the extracts produced from Aurantiochytrium sp. biomass. A full factorial experimental plan was performed, comprising three factors (pressure, temperature, and flow rate) and two levels (200−300 bar, 40−80 °C, and 6–12 gmin−1, respectively). The maximum and minimum experimental results were ηTotal = 2.1 and 13.4 wt.%, CDHA= 27.3 and 39.3 wt.%, TPC =1.19 and 2.24 mgGAE g−extract 1 , and AOC = 0.3 and 1.4 mg g− TEAC extract 1. Under the studied experimental conditions, increasing pressure up to 300 bar is the optimum to rise both ηTotal and CDHA. Temperature increase from 40 to 80 °C leads to opposing effects: it favors the concentration of phenolics in the supercritical extracts at the expenses of decreasing DHA content and total yield. Surface models were adjusted to ηTotal, CDHA and TPC data, and the goodness of the fits ranged from coefficients of determination of 0.752-0.711 (TPC) to 0.997-0.994 (CDHA). Under optimized conditions, supercritical extracts exhibited a DHA content more than 3.5-fold richer than fish oil, and 7.9-fold richer than the best alternative microalgae species (Pavlova lutheri) found in the literature.